A visual robot-programming environment for multidisciplinary education - Cross, Jennifer; Bartley, Christopher; Hamner, Emily; Nourbakhsh, Illah (2013 IEEE International Conference on Robotics and Automation, 2013)
Arts & Bots is an educational program that aims to broaden diversity and participation in technology by integrating arts and crafts with robotics. Arts & Bots is a flexible program that can be integrated into in-school and out-of-school programs in many subject areas. This paper describes the visual programming environment developed for Arts & Bots and its goals of low barriers to entry, classroom compatibility, supporting student acquisition of computational thinking skills, and enabling complex robot behaviors. The authors also compare and contrast the programming environment with other popular visual programming environments, namely Scratch, Alice and LEGO NXT-G.